Development of an integrated library system for Ramon Magsaysay (Cubao) High School Library - Baylas, Bianca Rei T. (2009)
RMCHS is aiming to enhance computer literacy and enable them to cope with changes brought about by modernization and industrialization. However, without a system, there will be no way to effectively and efficiently utilize the services of the library to realize their goals. And by developing a system, there'll be a way to understand problems and discover opportunities in the area of technology.